Acute myeloid leukemia with central nervous system involvement successfully treated with gilteritinib - Koyama, Gentaro; Kawaguchi, Takeharu; Sato, Takumi; Hamada, Chihiro; Hara, Satoru (Rinshō ketsueki, 2024)
A 69-year-old woman was referred to our hospital due to hyperleukocytosis. We diagnosed acute myeloid leukemia and started induction therapy with the CAG regimen (aclarubicin, cytarabine and filgrastim). However, the patient was refractory to the initial treatment and developed quadriplegia, and a cerebrospinal fluid (CSF) test showed elevated blasts. We then performed intrathecal chemotherapy, and the number of blasts in CSF gradually decreased. But only two cycles of intrathecal therapy were possible due to severe methotrexate-induced mucositis. The leukemia cells had fms-like kinase 3-internal tandem duplication (FLT3-ITD), so we started treatment with oral gilteritinib. The patient then achieved hematological complete remission. Her paralysis was also resolving, and the CSF was clear of blasts for more than 6 months. Some reports show that gilteritinib may penetrate the CNS, and this case also supports the effectiveness of gilteritinib on CNS leukemia.